Bimbingan Rohani Islam dalam Meningkatkan Ibadah Shalat Pada Pasien Rawat Inap - Komaruddin Komaruddin (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
ABSTRACT: This researcher aims to describe the awareness of worship in inpatients and the role of Islamic spiritual guidance in increasing awareness of carrying out worship (Salat) in inpatients. This research is motivated by the low understanding and awareness of the community to continue to carry out worship even though they are sick and being treated in a hospital. The approach used in this research is a qualitative approach with a type of field research. The subjects of this study were three inpatients in the internal medicine ward. Data collection techniques, namely the method of observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that prior to carrying out the guidance of the three subjects they did not have an understanding of the procedures for praying when they were sick, they did not have awareness of the importance of praying even though they were sick. Islamic spiritual guidance is carried out through three stages, namely the preliminary stage (establishing closeness with patients and identifying problems), the core stage (guidance on procedures for worship/praying when sick, motivation to increase awareness of praying when sick). Islamic spiritual guidance has an important role in raising awareness of worship in inpatients, this is evidenced by changes in knowledge of procedures for purification and prayer when they are sick, the emergence of a desire to pray and a commitment to continue praying even though they are sick. KEYWORDS: Islamic Spiritual Guidance, Worship Awareness, patient